Five new species of Acanthobothrium van Beneden, 1849 (Cestoda: Tetraphyllidea) in elasmobranchs from the northwest Atlantic and Gulf of Mexico with first records from smooth-hound sharks and guitarfish - Vardo-Zalik, Anne M.; Campbell, Ronald A. (Zootaxa, 2011)
Five new species of Acanthobothrium van Beneden, 1849 are described from elasmobranchs from Atlantic coastal waters of the United States and western Gulf of Mexico. Acanthobothrium cairae sp. nov., a category 3 species, from the roughtail stingray Dasyatis centroura (Mitchill), from New England coastal waters of Narragansett Bay, Rhode Island is differentiated from congeners by a combination of characteristics including hook lengths, testis number (82–166) and distribution, bilobed ovary and 8 large muscle fascicles symmetrically encircling the reproductive organs. Four new category 1 species of Acanthobothrium from four new host species from the Gulf of Mexico are Acanthobothrium lentiginosum sp. nov. from the rhinobatid (guitarfish), Rhinobatos lentiginosus Garman; Acanthobothrium schalli sp. nov. from two species of triakid sharks, Mustelus canis canis Mitchill and M. norrisi Springer; and Acanthobothrium ulmeri sp. nov. and A. westi sp. nov., both from the skate Raja texana Chandler (Rajidae). Acanthobothrium floridensis Goldstein, 1964 is reported from a new host, R. texana off the Texas coast in the western Gulf of Mexico, a new locality for this species. These species are differentiated by a combination of characters including size, bothridial size, total hook length, ratio of total hook length to bothridium length, ratio of bothridial length to cephalic peduncle length, ovarian shape, position of the genital pore, testis number and distribution. Biogeographically these records from sharks and the guitarfish are new for Acanthobothrium and add two new host families to the distribution of Acanthobothrium in coastal waters of the western Atlantic Ocean. Acanthobothrium is now known to occur in six families of elasmobranchs in the Gulf of Mexico: skates (Rajidae), rays (Dasyatidae, Gymnuridae, Myliobatidae), sharks (Triakidae) and guitarfish (Rhinobatidae) making it the most diverse geographical region for these cestodes in the eastern coastal waters of North America.